Pendidikan Lingkungan Hidup di Sekolah Dasar Jepang - Galih Satrio Pamuji; Dwi Astuti Retno Lestari (J-Litera: Jurnal Kajian Bahasa, Sastra dan Budaya Jepang, 2022)
The purpose of this study was to determine the application of environmental education in elementary schools in Japan from the point of view of the actual curriculum and the hidden curriculum and the function of the curriculum in environmental education at the elementary school level in Japan. The method used in this research is a literature study method by collecting data through online scientific journal articles. This study uses Sanjaya's actual curriculum theory and Subandijah's hidden curriculum theory to determine the classification of the actual and hidden curriculum in the application of environmental education. The results of this study are the application of environmental education is applied in the classroom and outside the classroom, then each application is included in the actual curriculum and hidden curriculum based on the perspective of Educational for Sustainable Development (ESD). Environmental education here also contains two curriculum functions according to Mcneil, the exploration function and specialization.